Oficinas de fandango caiçara como vivência de educação popular na Associação dos Jovens da Jureia-AJJ/Barra do Ribeira Iguape SP: reafirmando o potencial das comunidades tradicionais caiçaras. - Franco, Paulo Cesar (Universidade Federal de São Carlos, 2015)
This dissertation is a research study that sought to reveal the potential of caiçara culture starting from the knowledge of experience which has resulted in making the workshops of caiçara fandango conceived as experience of Popular Education at the Youth Association of Jureia-AJJ, entity located in the community Barra do Ribeira, in the city of Iguape, SP, to reaffirm the potential of traditional caiçara communities. Divided into three chapters, research primarily reflected the process of formation and development of traditional caiçara communities of Jureia in four different times, starting from the Ancient Time, Real Estate Speculation Time, Time Nuclebrás and Ecological Station Time. In the second chapter we discussed the relationship between the ecologies of knowledge proposed by Boaventura de Sousa Santos and the caiçara way of life as an alternative to Western rationality model. The third chapter was aimed at reflection and analysis of caiçara fandango workshops in which were translated the steps of building the fiddle as a popular education process that express and empower caiçara community of Jureia through the mystic and the way of doing fandango.
Fandango wokshops caiçara as education experience people in the pool of youth Jureia-Ajj / riverside bar - Iguape/SP: reafirming potential of the traditional caiçaras
Keywords: Oficina de Fandango Caiçara; educação popular; Comunidades Tradicionais Caiçaras da Jureia; educação popular; Fandango. Iguape (SP); Iguape SP História; Caiçara Fandango Workshop; Popular Education; Traditional Caiçara communities of Jureia; CIENCIAS HUMANAS::EDUCACAO